Distinct transcriptional and processing regulations control miR167a level in tomato during stress. Issue 1 (2nd January 2018) - Jodder, Jayanti; Das, Rohit; Sarkar, Deepti; Bhattacharjee, Payel; Kundu, Pallob
ABSTRACT: Besides their definite role in plant developmental processes miR167 also serve as mediator of stress response. Although differential expression of miR167 occurs during stresses, the regulatory-mechanism of biogenesis remained elusive. Therefore, using tomato as the model plant we have explored the mechanism of regulation of miR167a expression during stresses. Fungus or virus infections and exposure to cold stress raised the level of miR167a expression. Whereas, salt, drought and heat treatments resulted in the downregulation, indicating different stresses activated alternative mechanisms for miR167a regulation. Interestingly, the relative expression level of precursors in control versus temperature stressed plants differed from the pattern observed in the mature miR167a expression, suggesting that both transcriptional and processing regulation were important for biogenesis. The promoter-regulatory sequence of the major isoform MIR167a harbours several development and stress-related regulatory sites. Accordingly, promoter assays using transient transformation and transgenic tobacco plants proved stress-dependent regulation of the promoter. Further analyses corroborated the role of tomato DREB2A protein in the transcriptional regulation during temperature stress. Finally, in vitro assays established the importance of processing factors in cold-stress dependent efficient processing of MIR167a precursors. These data confirm distinct role of transcriptional and processing machinery in stress-influenced regulation of tomato miR167a biogenesis.